Instructional Leadership Style at MAN 1 Samarinda - Suratman Suratman (UIN Sultan Aji Muhammad Idris Samarinda, 2021)
The aim of this research is to describe instructional leadership as one of the leadership styles in the context of Madrasah Aliyah teaching and learning, typically at MAN 1 Samarinda, East Kalimantan. In-depth interviews with the school principal and representative teachers from all levels were conducted in order to dig information regarding the research focus. Additionally, document analysis is also used to support the findings gained from in-depth interviews specifically related to the document of school vision and mission and supervision of teachers' performance. As a result, three dimensions of instructional leadership exist in the implementation of instructional leadership at MAN 1 Samarinda, i.e. the school principal supports in terms of the implementation of school vision and mission, management of school program, and positive teaching and learning climate. Even though this research gains positive results regarding with the implementation of instructional leadership, some previous studies in this research reveal that there are quite many formal schools who are still lack of knowledge concerning with leadership styles especially instructional leadership. Therefore, the pedagogical implication of this research findings drives the involvement of the government in supporting school principal in any formal institution, especially in enriching their knowledge in implementing appropriate leadership styles. Research novelty and pedagogical implications are discussed further in this research.